Hot Topics in Infection and Immunity in Children VI - Finn, Adam.; Finn, Adam.; Curtis, Nigel.; Curtis, Nigel.; Pollard, Andrew J.; Pollard, Andrew J. (Advances in Experimental Medicine and Biology,, 2010)
Course covers topics in infectious diseases in children and is intended for Pediatric Infectious disease trainees, trainers, and all those who manage children with infections. Each of the chapters in this book is based on a lecture given at the sixth "Infection and Immunity in Children" course, held at the end of June 2008 at Keble College, Oxford. Thus, it is the sixth book in a series that provides succinct and readable updates on just about every aspect of the discipline of Pediatric Infectious Diseases.